Semiochemical screening for the cacao mirid bug (Helopeltis bakeri Poppius) - Tavera, Mary Angelique A. (Animo Repository, 2019)
Cacao is a globally important crop from which chocolates are produced fro. Cacao only grows in the equatorial region and the Philippines is among the few countries which can cultivate it. However, the local cacao production is threated by insect infestations which can significantly decrease the yiled and quality of cacao pods. The insect Helopeltis bakeri Poppius (Hemiptera: Miridae) or commonly called as cacao mirdi bug (CMB) is one of the major insect pests of cacao, together with the cacao pod borer (Canopomorpha cramella). The CMB feeds on the cacao pods resulting to damage in the pods rendering them unusable. Thus, effective but environment friendly measures are needed in order to control and manage the infestation caused by the CMB. This alternative pest control strategy is called integrated pest management (IPM). One technique in IPM is the use of semiochemicals where natural chemical signals are used to confuse and disorient the pest. In this study, identification of the semiochemicals that attracts the CMB for feeding and mating are determined by headspace analysis using solid phase microextraction (SPME) coupled with gas-chromatography-mass spectroscopy (GC-MS). From the volatile profiles, common terpene compounds were determined. Olfactometry analysis using lab reared CMBs elicits a positive response towards the compound caryopphyllene. The suspected sex pheromone, alpha-pinene, was detected in the abdomen of a 96 hours old female virgin and bioassay results exhibit signs of attraction of the male virgin mirid bug. Data gathered from this study may help convince farmers to transition from old farming methods to a more sustainable cacao farming practices such as IPM.